Peran Budaya Organisasi Berbasis Nilai Keislaman dalam Meningkatkan Mutu Pendidikan - Tiara Amalia; Subiyantoro Subiyantoro (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyse the role of organisational culture in improving the quality of education in Islamic-based secondary schools. This study is motivated by the importance of organisational culture as a driving force in shaping a positive learning environment, enhancing teacher professionalism, and strengthening the participation of the entire school community. The research approach uses a qualitative method with a case study design conducted at SMP Negeri 4 Langsa. Data were collected through in-depth interviews, participatory observation, and documentation study, then analysed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and thematic conclusion drawing.The results of the study indicate that the organisational culture at SMP Negeri 4 Langsa stems from the values of religiosity, discipline, and togetherness that are internalised in school routines. These values create a conducive learning climate, strengthen teacher professionalism through collaboration and learning reflection, and foster active participation from the entire school community. The participatory leadership of the principal is a key factor in fostering a sense of ownership and collective responsibility for the quality of the institution. A religious and inclusive work culture has proven to be the foundation for improving the effectiveness and sustainability of education. Theoretically, this article contributes to expanding the concept of educational organisational culture by adding spiritual and participatory dimensions as integral elements in the development of Islamic value-based school quality. Practically, the results of this study provide an implementable model for educational institutions to integrate religious values into management systems and teacher professional development as an effort to build a superior and character-based educational ecosystem.